Using Addressing Terms to Promote World-Englishes in Indonesia - Nurvita Wijayanti; Trie Arie Bowo; Dini Wulansari (Lingua Cultura, 2023)
The research were to analyze the addressing terms used in Indonesian society relating to the World-Englishes movement and to analyze the process of the World-Englishes movement through the use of the addressing terms. Therefore, the research aimed to describe the movement process, especially in Indonesian society, by looking at how the students addressed the lecturers. The descriptive qualitative approach was applied by having an interview with eight universities in Indonesia and the chatting activities between the students and the lecturers. The postcolonial theory was used to show the ownership of English. The research concludes that some diction is only understood by Indonesian people speaking English. Therefore, those terms of addressing exclusively belong to the Indonesian language. However, it can be an encouraging signal that English belongs to not only the inner circle but also the expanding circle.